SysFinder: A customized platform for search, comparison and assisted design of appropriate animal models based on systematic similarity. (20th May 2017) - Yang, Shuang; Zhang, Guoqing; Liu, Wan; Wang, Zhen; Zhang, Jifeng; Yang, Dongshan; Chen, Y. Eugene; Sun, Hong; Li, Yixue
Abstract: Animal models are increasingly gaining values by cross-comparisons of response or resistance to clinical agents used for patients. However, many disease mechanisms and drug effects generated from animal models are not transferable to human. To address these issues, we developed SysFinder (http://lifecenter.sgst.cn/SysFinder ), a platform for scientists to find appropriate animal models for translational research. SysFinder offers a "topic-centered" approach for systematic comparisons of human genes, whose functions are involved in a specific scientific topic, to the corresponding homologous genes of animal models. Scientific topic can be a certain disease, drug, gene function or biological pathway. SysFinder calculates multi-level similarity indexes to evaluate the similarities between human and animal models in specified scientific topics. Meanwhile, SysFinder offers species-specific information to investigate the differences in molecular mechanisms between humans and animal models. Furthermore, SysFinder provides a user-friendly platform for determination of short guide RNAs (sgRNAs) and homology arms to design a new animal model. Case studies illustrate the ability of SysFinder in helping experimental scientists. SysFinder is a useful platform for experimental scientists to carry out their research in the human molecular mechanisms.